∫ − 2 π 2 π 1 + e x x 2 cos x d x = a π n − b
The equation above holds true for integers a , b and n . Find a + b + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nicely done sir! +1
@Md Zuhair i liked ur status dude . i recently gave Mains and realised the truthness in ur status
Log in to reply
Ya, Its not my quote by the way, I find it in quora, By the way, whats ur estimated score in Mains?
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Integration Tricks
I = ∫ − 2 π 2 π 1 + e x x 2 cos x d x = 2 1 ∫ − 2 π 2 π 1 + e x x 2 cos x + 1 + e − x ( − x ) 2 cos ( − x ) d x = 2 1 ∫ − 2 π 2 π 1 + e x x 2 cos x + e x + 1 e x x 2 cos x d x = 2 1 ∫ − 2 π 2 π x 2 cos x d x = 2 1 x 2 sin x ∣ ∣ ∣ ∣ − 2 π 2 π − 2 1 ∫ − 2 π 2 π 2 x sin x d x = 4 π 2 + x cos x ∣ ∣ ∣ ∣ − 2 π 2 π − ∫ − 2 π 2 π cos x d x = 4 π 2 − sin x ∣ ∣ ∣ ∣ − 2 π 2 π = 4 π 2 − 2 Using the identity: ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x By integration by parts By integration by parts again
⟹ a + b + n = 4 + 2 + 2 = 8